The Role of Different Organism, Task and Environment Constraints in Coincidence Anticipation Timing Accuracy - Shahzad Tahmasebi Boroujeni; Fariba Hasan barani; Elham Hatamishahmiri (University of Tehran, 2017)
Perceptual-motor skills play a vital role in many tasks of daily life and sports skills. The measurement of coincidence anticipation timing ability is a method to evaluate perceptual and perceptual-motor skills. Thus, the main aim of the present study was to investigate the role of different organism, task and environment constraints in coincidence anticipation timing accuracy. For this purpose, 30 female adolescents (17-15 years old), young (20-40 years old) and elderly (60-80 years old) participated in 4 tests of coincidence anticipation timing. The tests included a coincidence anticipation timing task with green (1), blue (2), red (3) color background and an additional environment constraint (4) and participants had to coincide with the arrival of the stimulus in the target point and press the corresponding key. For data analysis, mixed ANOVA (3*4), 4 one-way ANOVA and 3 ANOVA with repeated measures were used for each group with adjusted Bonferroni. Statistical analysis showed a significant difference in test 1, 3 and 4 (P≤0.0125). Also, all groups showed a significant reduction in performance when the background color changed from green to red and the addition of the secondary task (P≤0.017). In addition, results indicated that the elderly group had the weakest performance compared with the adolescent and young groups and the reason might be a weakness in perceptual-motor systems related to age increase. Finally, different coincidence anticipation training programs were recommended for athletes, elderly and patients with perceptual-motor system weakness.